Bauhinia Spp.,- Kachnar : Medicinal Plant Biodiversity, Geographical Distribution, Bioactive Phytochemical Constituents And Their Ethno-Pharmacology, Therapeutics Medicinal Values - Sagar, Pawan Kumar; S, Sajwan; Murugeswaran, R (Asian Journal of Pharmaceutical Research and Development, 2025)
Ethno-Pharmacological, bioactive phytochemical constituents, therapeutic uses, geographical distribution, medicinal potent values studies of ASU herbal single drugs / products remains a significant challenging task on global levels. There needs to be more than the advance investigation research studies and screening scientific research data’s studies to emphasized and explored of ethno-pharmacology and therapeutic medicinal potent values of ASU plants/ products authentication, medicinal and therapeutics important aspects. Bauhinia Spp.- BV,BP,BB,BA,BT,BR, Kachnar are one of the medicinal plants used to treat and cure of various therapeutic illness of public mankind from since ancient time. This study aims to evaluate the bioactive phytochemical constituents, Ethno-Pharmacological, geographical distribution, therapeutic medicinal potent values, an comprehensive review studies of the plant of Bauhinia Spp.- BV,BP,BB,BA,BT,BR. As per the literature, this genus possesses antimicrobial, antifungal, antidiarrheal, antistress, antioxidant, nephroprotective, anticancer, hepatoprotective, antidiabetic, anti-inflammatory, and antidepressant activities commonly both In-vitro and In-vivo, due to the presence of Alkaloids, flavonoids, steroidal, glycosides, terpenoids, tannin, phenolic, saponins, lignins, proteins and phenolic acids, bauhinioxepins, chromanones, compounds and Quercetin, β-sitisterol (Anticancer and Antitumor) bioactive compounds. However, more research is needed to explore the In-vivo clinical evaluation for their future uses application in treating various ailments for beneficial to public, mankind. Keywords: Bauhinia Spp.- BV,BP,BB,BA,BT,BR., bioactive phytochemical constituents, Ethno-Pharmacological, geographical distribution, Biodiversity, and therapeutic medicinal potential values, electronic search engine databases.